Individualized accelerated isotoxic concurrent chemo-radiotherapy for stage III non-small cell lung cancer: 5-Year results of a prospective study. (June 2019) - De Ruysscher, Dirk; van Baardwijk, Angela; Wanders, Rinus; Hendriks, Lizza E.; Reymen, Bart; van Empt, Wouter; Öllers, Michel C.; Bootsma, Gerben; Pitz, Cordula; van Eijsden, Linda; Dingemans, Anne-Marie C.
Highlights: With isotoxic radiotherapy dose escalation given concurrently with chemotherapy in patients with stage III NSCLC, toxicity was indeed as predicted and fairly low, but dose escalation could only be achieved in a minority of patients. Local failure rates as well as the overall survival were similar to those reported with conventional radiotherapy. Abstract: Background: Stage III non-small cell lung cancer (NSCLC) still has a poor prognosis. Prior studies with individualized, accelerated, isotoxic dose escalation (INDAR) with 3D-CRT showed promising results, especially in patients not treated with concurrent chemo-radiotherapy. We investigated if INDAR delivered with IMRT would improve the overall survival (OS) of stage III NSCLC patients treated with concurrent chemotherapy and radiotherapy. Patients and methods: Patients eligible for concurrent chemo-radiotherapy were entered in this prospective study. Radiotherapy was given to a dose of 45 Gy/30 fractions BID (1.5 Gy/fraction), followed by QD fractions of 2 Gy until a total dose determined by the normal tissue constraints. The primary endpoint was OS, secondary endpoints were loco-regional relapses and toxicity. Results: From May 4, 2009 until April 26, 2012, 185 patients were included. The mean tumor dose was 66.0 ± 12.8 Gy (36–73 Gy), delivered in a mean of 39.7 fractions in an overall treatment time of 38.2 days. The mean lung dose (MLD) was 17.3 Gy. The median OS was 19.8 months (95% CI 17.3–22.3) with a 5-year OS of 24.3%. Loco-regional failures as first site of recurrence occurred in 59/185 patients (31.8%). Isolated nodal failures (INF) were observed in 3/185 patients (1.6%). Dyspnea grade 3 was seen in 3.2% of patients and transient dysphagia grade 3 in 22%. Conclusions: INDAR with IMRT concurrently with chemotherapy did not lead to a sign of an improved OS in unselected stage III NSCLC patients.